Association of Age And Gender Distribution of Patients Reported with Open Apex in Maxillary Central Incisor - Balaji V1 , Surendar Sugumaran2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Usually open apex is associated with young people who develop early cavities, have a morphologicalanomaly or have suffered a dental trauma that prematurely halts root development The aim of this study isto assess the association of age and gender distribution of patients reported with Open apex in maxillarycentral incisor. The study setting is mainly a type of university based and a single centered study. Thisretrospective study examined the record of patients from june 2019 to april 2020 who underwent treatmentat saveetha dental college, chennai. Patients’ details were collected to assess the association of age andgender distribution of patients reported with Open apex in maxillary central incisor. A total of 270 patientdetails were evaluated. Patients were divided into 3 groups. Below 18 years, 18 to 50 years and above 50years. Patients records were reviewed and then data was extracted. Data was recorded in excel and laterexported IBM SPSS software (Version 21: IBM Corporation NY USA). Pearson chi square test was doneto statistically analyze the data. Patients of all age groups were included in this study. Around 40.15% ofthe patients were at the age group of 10-20 years, 21.19% were between the age of 20-30 years, 22.30%were between the age group of 30-40 years and 16.36% of the patients were at the age group of 40-50 years.Around 60.2% and 39.8% reported with open apex in 11 and 21 respectively of which 51.7% male and48.3% female patients respectively. Within the limits of this study,the age group of 10 - 20 years had beendiagnosed with most number of open apices in Maxillary central incisors.Which were 65 patients (24.16%)in 11 and 43 patients (15.99%) in 22 respectively. Majority of patients with age group 10-20 years reporteda higher incidence of open apex than other age groups